Genome-wide association analyses of autoimmune hypothyroidism reveal autoimmune and thyroid-specific contributions and an inverse relationship with cancer risk - Reeve, Mary Pat; Kanai, Masahiro; Graham, Daniel B.; Karjalainen, Juha; Luo, Shuang; Kolosov, Nikita; Adams, Cameron; Ritari, Jarmo; Karczewski, Konrad J.; Kiiskinen, Tuomo; Jiang, Yu; Fuller, Zachary; et al. (Springer Nature, 2026)
The high prevalence (>5%) of autoimmune hypothyroidism (AIHT) provides a unique opportunity to dissect genetic contributions to systemic and organ-specific autoimmunity. Here we performed a genome-wide association meta-analysis of 81,718 AIHT cases in FinnGen and the UK Biobank, identifying 418 independent signals (P < 5 × 10-8). At 48 of these loci, a protein-coding variant is, or is highly correlated (r2 > 0.95) with, the lead variant, including Finnish-enriched coding variants in LAG3, ZAP70 and TG. We demonstrated that ZAP70:T155M reduces T cell activation and broadly compare large-scale scans of nonthyroid autoimmunity and thyroid-stimulating hormone levels with a Bayesian classifier to assign loci into distinct groupings, estimating that 38% are involved in general autoimmunity whereas 20% are thyroid specific. We further identified substantial antagonistic pleiotropy, with 10% of AIHT loci showing a consistent protective effect against skin cancer. The AIHT results, including numerous genes encoding checkpoint proteins, support the causal role of natural immune variation influencing cancer outcomes.